Back Cover: Stereoselective Photopolymerization of Tetraphenylporphyrin Derivatives on Ag(110) at the Sub‐Monolayer Level (Chem. Eur. J. 44/2014). Issue 44 (27th October 2014) - Basagni, Andrea; Colazzo, Luciano; Sedona, Francesco; Di Marino, Marco; Carofiglio, Tommaso; Lubian, Elisa; Forrer, Daniel; Vittadini, Andrea; Casarin, Maurizio; Verdini, Alberto; Cossaro, Albano; Floreano, Luca; et al.
<x xml:space="preserve">Abstract</x> Cold regions (the mountain chain in the illustration) and warm areas (the beach in the foreground) represent the temperature ramp applied to obtain extended molecular wires under illumination at the sub‐monolayer level. The transhumance of amino‐functionalized porphyrins along the close‐packed atomic rows (the parallel roads) of the cold Ag(110) surface ends at the beach, where light induces their union (covalent bonding) as soon as they approach each other. For more details, see the Full Paper by A. Basagni et al. on page 14296 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>